Primary and maternal 3‐methylcrotonyl‐CoA carboxylase deficiency: insights from the Israel newborn screening program. Issue 2 (13th November 2015) - Rips, Jonathan; Almashanu, Shlomo; Mandel, Hanna; Josephsberg, Sagi; Lerman‐Sagie, Tally; Zerem, Ayelet; Podeh, Ben; Anikster, Yair; Shaag, Avraham; Luder, Anthony; Staretz Chacham, Orna; Spiegel, Ronen
Abstract: Background: 3‐Methylcrotonyl‐CoA carboxylase deficiency (3MCCD) is an inborn error of leucine catabolism. Tandem mass spectrometry newborn screening (NBS) programs worldwide confirmed 3MCCD to be the most common organic aciduria and a relatively benign disorder with favorable outcome. In addition, several asymptomatic 3MCCD mothers were initially identified following abnormal screening of their healthy babies and were appropriately termed maternal 3MCCD. Methods: This is a retrospective study that summarizes all the clinical, biochemical, and genetic data collected by questionnaires of all 3MCCD individuals that were identified by the extended Israeli NBS program since its introduction in 2009 including maternal 3MCCD cases. Results: A total of 36 3MCCD subjects were diagnosed within the 50‐month study period; 16 were classified primary and 20 maternal cases. Four additional 3MCCD individuals were identified following sibling screening. All maternal 3MCCD cases were asymptomatic except for one mother who manifested childhood hypotonia. Most of the primary 3MCCD individuals were asymptomatic except for two whose condition was also complicated by severe prematurity. Initial dried blood spot (DBS) free carnitine was significantly lower in neonates born to 3MCCD mothers compared with newborns with primary 3MCCD ( p = 0.0009). Most of the mutations identified in the MCCC1 and MCCC2 genes were missense, five of them were novel. Conclusions: Maternal 3MCCD is more common than previously thought and its presence may be initially indicated by low DBS free carnitine levels. Our findings provide additional confirmation of the benign nature of 3MCCD and we suggest to exclude this disorder from NBS programs.